Identifying Contextual Workplace Stressors in a Division of Plastic and Reconstructive Surgery - Viola Goodacre, MPS, MSc; Karthik Adapa, MD, PhD; Elizabeth Kwong, MS; Lisa M. Vizer, PhD; Chao-Chin Liu, MS; Nadia Charguia, MD; Caprice Greenberg, MD, MPH; Lynn A. Damitz, MD, FACS; Damian McHugh, MD; Lukasz M. Mazur, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Healthcare professionals in plastic and reconstructive surgery (PRS) face unique stressors that contribute to burnout, increasing the risk of errors and compromising patient care. Despite this, there is limited research on PRS burnout in the United States. This study aimed to measure burnout rates and identify high-impact improvement targets within a PRS division at a US academic medical center. Methods:. A sequential mixed-methods study was conducted, involving systems analysis and contextual design methods. All surgeons (n = 5) and nonsurgeons (n = 9) were invited to participate (total n = 14). Burnout rates were measured, and workplace stressors were identified using surveys, focus groups, and contextual inquiries. High-impact, low-effort improvement targets were determined through impact-effort matrices. Results:. Survey data from 13 respondents revealed an 85% burnout rate. Three focus groups and 14 contextual inquiries were conducted. After 13 participants validated and prioritized 2 affinity diagrams and provided 24 high-priority stressors, 8 respondents completed 2 surveys that yielded 6 high-impact/low-effort targets for organizational improvement efforts. Conclusions:. This study highlights the high prevalence of burnout in PRS and identifies specific improvement targets for both surgeons and nonsurgeons. Findings suggest strategies such as improving respect and recognition for surgeons and streamlining clinic flow for nonsurgeons. Implementing these targeted improvements can enhance the well-being of healthcare professionals and ultimately improve patient care. The study’s methods can be replicated by other healthcare organizations to identify and address burnout-related issues effectively.